DAMPAK SUPLEMENTASI MIKRONUTRIEN TERHADAP KENAIKAN BERAT DAN PANJANG BADAN ANAK GAGAL TUMBUH DI WILAYAH PESISIR SEMARANG - Siti Fatimah Pradigdo; S.A. Nugraheni (Media Gizi Mikro Indonesia, 2023)
ABSTRACT According to Unicef report and several studies, its shows that complementary food breast milk made at the household level tends to lack vitamins and minerals (vitamin A, Zn, and iron) which contribute to children’s growth. Quality of complementary food for breast milk, micronutrients deficiencies are determining factor’s for Baduta’s failure to grow. . The research objective is to determine the effect of micronutrient supplementation on body weight and length of children failing to thrive in the Semarang Coastal Area. This type of research is Quacy Experimental with a pretest posttest group design. Subjects have been kids aged 12-23 months with weight gain throughout two months of observation at the fifth percentile of the WHO standard. The number of subjects was 72 non probability sampling used to be then divided into three intervention groups, namely: Zn syrup supplementation 10 mg, supplementation of iron syrup 7.5 mg + vitamin B complex, and supplementation of Zn syrup 10 mg and iron syrup 7.5 mg + vitamin B complex. The intervention was once given for two months. The variables measured had been body weight and length, adequacy of macronutrients. The research instruments consisted of digital scales, an infantometer/microtoice, questionnaires, recall forms, nutrisurvey Statistical using Paired T-Test, Pearson Product Moment. Average weight gain over the two months of the study Zn group 0.34 ± 0.45 kg, iron+Vitamin B complex group 0.60 ± 0.73 kg, and Zn group with iron+Vitamin B complex 0.58 ± 0, 49 kg. The increase in body length of all intervention groups was > 1 cm. Test Paired T-Test there were significant differences in body weight and length before and after the intervention of all intervention groups (p<0.05). The Pearson Product Moment test found that the level of energy adequacy played a role in determining weight gain (p<0.05) in all intervention groups. The level of adequacy of macronutrients was not associated with an increase in body length (p>0.05) Micronutrient supplementation affects body weight and body length. Micronutrients contribute to body weight, but not to body length. It is recommended that Baduta’s mother’s education regarding feeding, can be accompanied by supplementation of Z, iron. ABSTRAK Berdasarkan llaporan UNICEF dan beberapa penelitian menunjukkan bahwa MP – ASI yang dibuat di tingkat rumah tangga cenderung kekurangan vitamin dan mineral (vitamin A, Zn dan Fe) yang berkontribusi terhadap pertumbuhan anak. Tujuan penelitian adalah untuk mengetahui pengaruh suplementasi mikronutrien terhadap berat berat dan panjang badan anak gagal tumbuh di Wilayah Pesisir Semarang Jenis penelitian adalah Quacy Experimental dengan Pretest Postest Group Design. Subyek adalah anak usia 12 – 23 bulan dengan kenaikan berat badannya selama 2 bulan pengamatan < persentil ke-5 standar WHO. Jumlah subyek 72 yang terpilih secara non probability sampling, kemudian dibagi dalam 3 kelompok intervensi yaitu: suplementasi sirup Zn 10 mg, suplementasi sirup Fe 7,5 mg + Vitamin B kompleks, dan suplementasi sirup Zn 10 mg dan sirup Fe 7,5 mg + vitamin B kompleks. Intervensi diberikan selama 2 bulan. Variabel yang diukur adalah berat dan panjang badan, kecukupan zat gizi makronutrien. Instrumen penelitian terdiri dari timbangan digital, infantometer/microtoice, kuesioner, form recall, nutrisurvey Uji statistik menggunakan Paired T-Test, Pearson Product Moment. Rerata pertambahan berat badan selama 2 bulan penelitian kelompok Zn 0,34 ± 0,45 kg, kelompok Fe+Vitamin B kompleks 0,60 ± 0,73 kg, dan kelompok Zn dengan Fe+Vitamin B kompleks 0,58 ± 0,49 kg. Kenaikan panjang badan semua kelompok intervensi > 1 cm. Uji Paired T-Test ada perbedaan bermakna berat dan panjang badan sebelum dan setelah intervensi semua kelompok intervensi (p<0,05). Uji Pearson Product Moment menemukan tingkat kecukupan energi turut berperan menentukan kenaikan berat badan (p<0,05) pada semua kelompok intervensi. Tingkat kecukupan makronutrien tidak berhubungan dengan kenaikan panjang badan (p>0,05). Suplementasi mikronutrien mempengaruhi berat badan dan panjang badan. Makronutrien memberikan kontribusi terhadap berat badan, tetapi tidak terhadap panjang badan. Disarankan edukasi ibu Baduta terkait pemberian makanan, dapat disertai dengan suplementasi Zn, Fe.